Transcriptional analysis of the amidase operon from Pseudomonas aeruginosa. - Wilson, S A (1995)
The transcriptional start point for the amidase structural gene (amiE) of Pseudomonas aeruginosa has been identified, and the promoter (pE) has been shown to function constitutively, as predicted for a system regulated by transcription antitermination. Northern (RNA) analysis results show that in cells grown under inducing conditions, a major 1.3-kb amiE transcript arises from pE, and in addition, a larger transcript of approximately 5.0 kb in length has been shown to derive from the same promoter, encoding all of the genes of the operon. DNA sequencing and S1 nuclease mapping have located a transcription terminator downstream of amiE, which terminates approximately half of the pE transcripts. Previously, two RpoN-dependent promoter-like sequences (pN1 and pN2) were identified upstream of the negative regulator gene, amiC, and we have now constructed a promoter probe vector which shows weak constitutive promoter activity within this region. This promoter would be expected to provide basal levels of expression of the amiC and amiR regulatory genes to allow induction of the system.